-1-2x-6x=-65

Simple and best practice solution for -1-2x-6x=-65 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1-2x-6x=-65 equation:


Simplifying
-1 + -2x + -6x = -65

Combine like terms: -2x + -6x = -8x
-1 + -8x = -65

Solving
-1 + -8x = -65

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + -8x = -65 + 1

Combine like terms: -1 + 1 = 0
0 + -8x = -65 + 1
-8x = -65 + 1

Combine like terms: -65 + 1 = -64
-8x = -64

Divide each side by '-8'.
x = 8

Simplifying
x = 8

See similar equations:

| 5x-4=30x+16 | | 6x-4(2-x)=14 | | -17=-2x-2x-5 | | 2=8x-32 | | 4(5x-4)+4=-10 | | -4=3x+7(-x-4) | | 15x+10=8x+38 | | -2x-8=-5x+28 | | 9(2n-1)=(8n+4)+3 | | 2(x-1)=24 | | 93=-6x+3(-2x-13) | | 8x-12+7=-3 | | 3x^2+30x-4=0 | | 4x+11=10x-7 | | z+5=-5 | | 4(3x-5)+x=z | | 11y-12=6y+8 | | 6y+4=2y+20 | | 5xa+7=c+a | | 4(3x-5)+x= | | 10x+5(z-12)=0 | | -3x-10=-2x+4 | | 0.6(j-2)=0.3l | | 20+x=2(20-2x) | | 14-d=45 | | x+2x+2x-30=5400 | | 8-n-3n=6 | | -6x+2y=5 | | 6x-2(-6x+3)=120 | | 2x+20=-3x+50 | | 4(x-3)+7=-3 | | 7x+2(3x+7)=144 |

Equations solver categories